Bimetallic Lanthanide Complexes Derived from Macrocycle-Appended m-Xylyl Derivatives: Synthesis and Spectroscopic Properties - Placidi, M; Natrajan, L; Sykes, D; Kenwright, A; Faulkner, S (2009)
A series of bimetallic lanthanide complexes was prepared from a bimacrocyclic system in which two DO3A units are linked by a m-xylyl unit appended with either a NO2 or an NH2 group (DO3A=1,4,7,10-tetraazacyclododecane-1,4,7-triacetic acid). The Nd-, Eu-, Tb- and Yb-complexes were all luminescent: time-resolved studies indicated that the lipophilic xylyl group restricts close approach of H2O to the metal centre. © 2009 Verlag Helvetica Chimica Acta AG.